What is democracy? A reconceptualization of the quality of democracy. Issue 1 (2nd January 2016) - Munck, Gerardo L.
Abstract : Works on the quality of democracy propose standards for evaluating politics beyond those encompassed by a minimal definition of democracy. Yet, what is the quality of democracy? This article first reconstructs and assesses current conceptualizations of the quality of democracy. Thereafter, it reconceptualizes the quality of democracy by equating it with democracy pure and simple, positing that democracy is a synthesis of political freedom and political equality, and spelling out the implications of this substantive assumption. The proposal is to broaden the concept of democracy to address two additional spheres: government decision-making – political institutions are democratic inasmuch as a majority of citizens can change the status quo – and the social environment of politics – the social context cannot turn the principles of political freedom and equality into mere formalities. Alternative specifications of democratic standards are considered and reasons for discarding them are provided.